Spray volumes and fungicide rates on Asian soybean rust control - Chechi,Amanda (2019)
ABSTRACT The aim of this study was to assess the effect of different spray volumes and fungicide rates on Asian soybean rust control. Experiments were conducted in the field and in the laboratory during 2014 and 2016. We varied the fungicide rates (45 + 52.5, 60 + 70 and 75 + 87.5 g a.i. ha-1 for the mixture trifloxystrobin + prothioconazole, and 45 + 22.5, 60 + 30 and 75 + 37.5 g a.i. ha-1 for azoxystrobin + benzovindiflupyr) and the spray volume (100, 150 and 200 L ha-1) for application on soybean plants in the field. Another experiment was conducted in the laboratory, using the recommended rates of the fungicides trifloxystrobin + prothioconazole (60 + 70 g a.i. ha-1) and azoxystrobin + benzovindiflupyr (60 + 30 g a.i. ha-1). The spray volume of 200 L ha-1 resulted in the best disease control only for the third out of three applications carried out in the field (control between 68.4% and 70.1%). However, there was no statistical difference in grain yield for all tested spray volumes when we used the recommended fungicide rates (3422, 3526 and 3601 kg ha-1) or higher rates (3529, 3586 and 3550 kg ha-1). The decrease in the fungicide rate directly implied reduced rust control for both experiments (20 to 39% in the field and up to 71.4% in the laboratory).